ADHERENCE TO A COMPREHENSIVE REHABILITATION PROGRAM AFTER CORONARY ARTERY BYPASS GRAFTING: A CHALLENGE FOR A PATIENT OR A PHYSICIAN? - Светлана Александровна Помешкина; Валентина Анатольевна Беззубова; Юлия Александровна Аргунова; Ольга Леонидовна Барбараш (Медицина в Кузбассе)
Aim – to assess the awareness of patients referred to elective coronary artery bypass grafting (CABG) about cardiac rehabilitation programs and to evaluate the adherence of cardiologists to appoint exercise outpatient cardiac rehabilitation to CABG patients.